The Impact of BRAF Mutation on the Recurrence of Papillary Thyroid Carcinoma: A Meta-Analysis - Xin Li (Cancers, 2020)
Previous meta-analyses indicated that the BRAF V600E mutation was associated with an increased recurrence rate of papillary thyroid carcinoma (PTC). However, with recent publications of large cohort studies, the need for an updated meta-analysis increases. Therefore, we conducted a comprehensive meta-analysis to assess the impact of the BRAF V600E mutation on PTC recurrences. We performed a literature search using PubMed, SCOPUS, the Cochrane Database of Systematic Reviews, and the Web of Science Core Collection, from their inception to May 31, 2020. The relevant studies compared recurrence rates using the hazard ratio (HR) of BRAF mutations; 11 studies comprising 4674 patients were identified and included. Recurrence rates in patients with the BRAF V600E mutation were comparable with BRAF wild-type patients (HR 1.16, 95% CI 0.78–1.71), after adjustment for possible confounders. In subgroup analysis, both geographical region (HRs for America, Asia, and Europe were 2.16, 1.31 and 0.66, respectively) and tumor stage (HRs for stage I and II were 1.51 and 4.45, respectively) can affect the HRs of the BRAF mutation for recurrence. In conclusion, the BRAF mutation does not increase the risk of recurrences in patients with PTC. Differences in the geographical region or tumor stage should be considered when interpreting the impact of a BRAF mutation on recurrence.